A Family of Key Agreement Mechanisms for Mission Critical Communications for Secure Mobile Ad Hoc and Wireless Mesh Internetworking. (23rd September 2010) - Askoxylakis, Ioannis G.; Tryfonas, Theo; May, John; Siris, Vasilios; Traganitis, Apostolos
Abstract : Future wireless networks like mobile ad hoc networks and wireless mesh networks are expected to play important role in demanding communications such as mission critical communications. MANETs are ideal for emergency cases where the communication infrastructure has been completely destroyed and there is a need for quick set up of communications among the rescue/emergency workers. In such emergency scenarios wireless mesh networks may be employed in a later phase for providing advanced communications and services acting as a backbone network in the affected area. Internetworking of both types of future networks will provide a broad range of mission critical applications. While offering many advantages, such as flexibility, easy of deployment and low cost, MANETs and mesh networks face important security and resilience threats, especially for such demanding applications. We introduce a family of key agreement methods based on weak to strong authentication associated with several multiparty contributory key establishment methods. We examine the attributes of each key establishment method and how each method can be better applied in different scenarios. The proposed protocols support seamlessly both types of networks and consider system and application requirements such as efficient and secure internetworking, dynamicity of network topologies and support of thin clients.